If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -3(3y + -7) + -1y = -3(y + -5) Reorder the terms: -3(-7 + 3y) + -1y = -3(y + -5) (-7 * -3 + 3y * -3) + -1y = -3(y + -5) (21 + -9y) + -1y = -3(y + -5) Combine like terms: -9y + -1y = -10y 21 + -10y = -3(y + -5) Reorder the terms: 21 + -10y = -3(-5 + y) 21 + -10y = (-5 * -3 + y * -3) 21 + -10y = (15 + -3y) Solving 21 + -10y = 15 + -3y Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '3y' to each side of the equation. 21 + -10y + 3y = 15 + -3y + 3y Combine like terms: -10y + 3y = -7y 21 + -7y = 15 + -3y + 3y Combine like terms: -3y + 3y = 0 21 + -7y = 15 + 0 21 + -7y = 15 Add '-21' to each side of the equation. 21 + -21 + -7y = 15 + -21 Combine like terms: 21 + -21 = 0 0 + -7y = 15 + -21 -7y = 15 + -21 Combine like terms: 15 + -21 = -6 -7y = -6 Divide each side by '-7'. y = 0.8571428571 Simplifying y = 0.8571428571
| 8.48x-2.6=-7.17x-7.1 | | h=55-20t-5t^2 | | -2y-7=15 | | 3/4(x-4)=2(x-1) | | -10v-10=9v-8 | | .25(n+2)=1 | | .40+.30(25-x)=.35(25) | | 8x-4x+2=x-4+6 | | 0.4(2c-30)=-0.8(c-4) | | x-6*2=24 | | (X+y+3z)-(4x-6y+z)= | | 90=w+w+(4w-6) | | 0.2(6c-48)=-0.6(c-2) | | 6y+2-y=8+4y-7 | | 2(n)=6-20 | | (2a+1)-a+2= | | 2t=5w-y | | -5x/520 | | 2t=5t-y | | 90=x+x-2 | | (X+y+4z)-(2x-6y+z)= | | 180=x+x+(x+3) | | 3/5m-5-1/2=1 | | 5/11a-3=16/11 | | 3/5m-5_1/2m=1 | | -2(x-7)=2(1+5x) | | -35/17=-49/34t | | 3x/7=.10 | | 3y/7=.10 | | -6(1+2v)+7(3v+6)=-6+7v-5v | | -2(1-2b)-3b=b-1 | | -2.4-5x-7.2-2x=-6x+8.6 |